Structural Diversity of Copper(II) Complexes with 9-Deazahypoxanthine and Their in Vitro SOD-Like Activity - Gáliková, Jana; Trávníček, Zdeněk (International journal of molecular sciences, 2015)
Two structurally different copper(II) complexes of the compositions [{Cu(9dhx)(H2O)3}2(µ-SO4)2] (1) and [Cu(9dhx)2(H2O)2(NO3)2]·H2O (2), involving 9-deazahypoxanthine (9dhx; 6-oxo-9-deazapurine; 9-deazahypoxanthine), have been prepared and characterized by elemental analysis, infrared and electronic spectroscopy, electrospray ionisation (ESI) mass spectrometry, thermogravimetric (TG) and differential thermal (DTA) analyses, and cyclic voltammetry. The X-ray structures of complexes 1 and [Cu(9dhx)2(H2O)2(NO3)2] (2a) revealed the distorted octahedral geometry in the vicinity of the copper(II) atoms, with the NO5 and N2O4 donor set, respectively. In the dimeric compound 1, the {Cu(9dhx)(H2O)3}2 units are bridged by sulfate groups with the Cu···Cu separation being 5.3446(2) Å. In both structures the 9dhx ligands are coordinated through the N3 atoms of the pyrimidine moieties. The SOD-like activity of complexes 1 and 2 was evaluated in vitro showing moderate effect, with the IC50 values equal to 18.20, and 53.33 μM, respectively.
Keywords: molekulární konformace; 6-oxo-9-deazapurine; in vitro SOD-like activity; Molecular Conformation; X-ray crystal structure; komplexní sloučeniny; Copper; copper(II) complexes; Superoxide Dismutase; krystalografie rentgenová; superoxiddismutasa; Crystallography, X-Ray; hypoxanthiny; Coordination Complexes; měď; hmotnostní spektrometrie s elektrosprejovou ionizací; Biocompatible Materials; spektroskopie infračervená s Fourierovou transformací; Electrochemical Techniques; Spectroscopy, Fourier Transform Infrared; biokompatibilní materiály; Spectrometry, Mass, Electrospray Ionization; 9-deazahypoxanthine; elektrochemické techniky; Hypoxanthines